Geometrical shape improvement of steel moulds by robot polishing process for polymer optic replication. Issue 1 (1st January 2018) - Almeida, Rui; Börret, Rainer; Pohl, Mario; Harrison, David K.; De Silva, Anjali K. M.
ABSTRACT: The quality of injection-moulded polymer optic parts depends on the surface finish of the respective mould. In order to improve the surface finish of the mould, it is important to use a tactical material removal, which allows a controlled correction of the mould's surface geometry. The aim of this work is to use a polishing correction technique to improve and correct the flatness of hardened steel samples in order to reduce the need for manual polishing. A polishing tool function is simulated from the contact between the tool and the hardened steel sample and used to determine the material removal rate per time. A feed profile is calculated, which allows the industrial robot to tactically control the material removal. It is observed that a correction improves the surface's flatness by up to 70%.